COVID-19 : perspectives on the pandemic and its incidence in dentistry = COVID-19 : perspectivas sobre la pandemia y su incidencia en odontología - Ramírez Mora, Tatiana 1975-
In December 2019, a novel coronavirus disease (COVID-19) presenting with pneumonia emerged in Wuhan, China. The ongoing spread of COVID-19 worldwide is creating enormous uncertainty. In particular, the dental profession is facing a major challenge. Due to the characteristics of dental settings, the risk of cross-infection is elevated between patients and dental staff. The present review aimed to briefly discuss the overview of the disease, including the basic science, epidemiology, symptoms, routes of transmission and several topics that the authors believe are binding and relevant to the dental practice. The guidelines adopted by governments and international organizations also address all dental associations to protect the health of the community and to contain the spread of COVID-19 infection until a vaccine or an effective/validated treatment becomes available.